2017
DOI: 10.1186/s12974-017-0902-x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 receptor type 1 is overexpressed in neurons but not in glial cells within the rat superficial spinal dorsal horn in complete Freund adjuvant-induced inflammatory pain

Abstract: Background: All known biological functions of the pro-inflammatory cytokine interleukin-1β (IL-1β) are mediated by type 1 interleukin receptor (IL-1R1). IL-1β-IL-1R1 signaling modulates various neuronal functions including spinal pain processing. Although the role of IL-1β in pain processing is generally accepted, there is a discussion in the literature whether IL-1β exerts its effect on spinal pain processing by activating neuronal or glial IL-1R1. To contribute to this debate, here we investigated the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 105 publications
6
16
0
Order By: Relevance
“…It has been reported that IL-1β can induce astrocytic activation and astrogliosis (Herx and Yong, 2001). Our earlier findings (Holló et al, 2017) also suggest that during inflammatory pain IL-1β can act on spinal neurons and astrocytes. It has been revealed that IL-1β induce cell type-specific response in the cells of the CNS due to a neuron specific isoform of the IL-1 receptor accessory protein (IL-1RAcP), which is a required receptor partner in IL-1 signaling (Huang et al, 2011).…”
Section: Introductionsupporting
confidence: 68%
“…It has been reported that IL-1β can induce astrocytic activation and astrogliosis (Herx and Yong, 2001). Our earlier findings (Holló et al, 2017) also suggest that during inflammatory pain IL-1β can act on spinal neurons and astrocytes. It has been revealed that IL-1β induce cell type-specific response in the cells of the CNS due to a neuron specific isoform of the IL-1 receptor accessory protein (IL-1RAcP), which is a required receptor partner in IL-1 signaling (Huang et al, 2011).…”
Section: Introductionsupporting
confidence: 68%
“…Previous reports found IL-1R1 expression in the spinal cord dorsal horn and DRG neurons, and assigned the neuronal IL-1R1 as the mediator of IL-1β-induced thermal and mechanical allodynia 19 22 . Another report showed IL-1 signaling in muscle fibers contributes to idiopathic inflammatory myopathies 14 , 41 .…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have suggested that IL-1β induces mechanical and thermal allodynia through neuronal IL-1R1 in the spinal cord dorsal horn 19 and dorsal root ganglia (DRG) 20 22 . Unexpectedly, IL-1R1 mRNA was not found in neurons or tissue macrophages in these regions in our IL-1R1 GR/GR and CX3CR1GFP-IL-1R1 GR/GR mice; this result was confirmed by NeuN, neurofilament and GFP immunolabeling (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although we and others (Wang et al, 2006;Holló et al, 2017) already showed that the spinal astrocytes express IL-1R1, we confirmed its expression on the cultured astrocytes (Figure 2A).…”
Section: Peripheral Inflammation Evoked By Cfa Injection Induced Elevsupporting
confidence: 65%